Grover Teeter with a player piano, 1963. - (:unkn) unknown (Forsyth County Public Library)
WSJ 6-30-63 p.A9.
Grover Teeter with a player piano, 1963.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth